Seismic response of multi-storey building using different vibration technique-A review - Karimi, Najia; Sarem, Roozbeh (International Journal of Innovative Research and Scientific Studies, 2021)
This review presents the high performance of failure-resistant structural device system for the sustainable and flexible buildings. Firstly, the motivation and basic principles as well as methodology of the developing device system are explicitly illustrated. Then, the structural detail and seismic response of base isolation systems, namely, lead Rubber Bearing (LRB), HDLRB isolators, viscous damper (Base Isolation with in-Parallel Dissipation system: BIPD) and sliding bearing isolator (Base Isolation with in-Series Sliding system: BISS) are summarized. The theoretical and experimental study results was shown that all four types of isolator system can be able to minimize damage after seismic an earthquake to the structural system. The viscous damper devices and energy dissipate as well as viscoelastic and fluid viscous dampening can be able to enhance the energy dissipation capacity of structural system under an earthquake loading. A placement of L shape, shear walls at the structural configuration plan is given more efficient behavior under seismic load than all other placements of shear walls at the building’s configuration. Many numerical specimens of tunnel form buildings were constructed and modelled to analyze and interpreted the dynamic and static cyclic response of structures against seismic force. The deformation of the dynamic response of tunnel form building was smaller by using Carbon Fiber Reinforced Polymer (CFRP) repairing and retrofitting method. Contradictory, the usage of base isolations, energy dissipation devices, shear walls and tunnel form buildings can enhance the efficiency of structures under seismic force by reducing the economic cost saving in their construction.